Modern Trends in Imaging VI: Raman Scattering in Pathology - Zachary J. Smith; Thomas R. Huser; Sebastian Wachsmann-Hogiu (Analytical Cellular Pathology)
Raman scattering is the inelastic scattering of light by chemical bonds, and can therefore show molecular specificity. It can be used both in pure spectroscopy mode, and in imaging mode. While many applications of Raman spectroscopy and imaging in the biomedical field have been so far demonstrated, the use of this technology for pathology applications is still in early stages. In this paper we review some of the most important recent developments in this field, including a description of relevant technologies, applications to molecular sensing, characterization of cells and tissues of interest, and disease detection via Raman scattering.